The relationships between cycling economy, pedalling effectiveness and cyclist`s musculoskeletal state - Rannama, I.; Reinpold, K.; Pedak, K.; Port, K. (World Congress of Performance Analysis of Sport XII, 2018)
The purpose of the study was to examine the relationships between road cyclists' musculoskeletal state, pedalling technique and metabolic economy (Gross Efficiency-GE) measured during incremental cycling exercise. The strength of knee extensor (KnEX) and flexor (KnFL) muscles of 30 competitive cyclists (19.0±2.1 y.; 1.82±0.06 m; 74.6±6.8 kg) were tested with a Humac NORM isokinetic dynamometer at angular speeds 60°/s (Maximal strength) and 180°/s (strength endurance and Fatigue Index (FI)). The core stability and for the fundamental movement abilities of cyclists were evaluated with Functional Movement Screen (FMS) test battery. After that cyclists performed incremental cycling exercise on Cyclus2 ergometer using their own racing bike equipped with Garmin Vector pedals. The ventilator, pedalling Torque Effectiveness (TE) and Smoothness (PS) parameters were captured continuously during the test. The GE was computed as ratio between mechanical cycling power and energy expenditure rate. The FMS score, thigh muscles strength characteristics, as well averaged GE, TE and PS values between aerobic (AeL) and anaerobic (AnL) work levels were registered for analysis in a later stage. Correlation and regression analysis were used to assess the relationships between the registered parameters. Tests revealed a moderate relationship between the GE and cyclists` ability to perform fundamental movements, evaluated by FMS test, as well as with KnEX FI and biomechanically effective pedalling technique. Multiple regression analysis of in-between subjects variation in GE the KnEX FI (Adj. R2 = 0.36) revealed common explanatory power with TE (Adj. R2 = 0.19), but adding the FMS score to the both parameters separately will increase the adjusted explanatory power of the model with 4% (Adj. R2 = 0.40) and 12% (Adj. R2 = 0.31) for KnEX FI and TE models respectively.